Penghayatan Lintas Budaya Pribumi Menyoroti Tionghoa dalam Sastra Indonesia - Pamela Allen (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
Talking about literary works written by Chinese-lndonesians, we can mention three kinds of works. First, as once discussed by writers like Leo Suryadinata and Claudine Salmon, are the works written since the 1870s until 1965, either mixed literature (tusheng huaren wenxue), written in the Malay language, or Chinese literature written in Chinese language. In general, the works reflect the life of the Chinese in Indonesia. Second are the works written in the New Order era, when Chinese culture was almost eliminated in Indonesia. Writers like Marga Tjoa Liang Tjoe and Mira Widjaja, who wrote under the names of Marga T. dan Mira W. (which hide their Chinese origin) identified themselves with Indonesian national culture Chinese culture or problems were not a priority in their works. Third are the works written in post-Suharto era The life and problems of the Chinese in Indonesia were brought up by some Indonesian writers, who are not Chinese or whose ethnicity is not important or not clear. Examples of such works include the short story "Clara by Seno Gumira Ajidama, the romance Ca Bau Kan by Remy Sylado, and the compilation of short stories Panggil aku Pheng Hwa by Veven Sp. Wardhana. In this paper, I will analize the "Chineseness of Veven Sp. Wardhana, a writer who claimed to speak for the Chinese people in his short stories.